The Rosalia Ranchof the Gottsch Cattle Company (Symphony in the Flint Hills, 2014)
From Cassoday to Latham with Rosalia in between, eastern Butler County is prime Flint Hills ranching country. Over the years the Rosalia vicinity has been home to a number of major ranching operations, including, among others, the Nuttles, the Dunns, the Liggetts, and the Jahrens. Added to that list in recent years is the Gottsch Cattle Company, comprising among its enterprises ranches, feedlots, and commodity trading. This ranch was the site of the 2014 Symphony in the Flint Hills performance.
Keywords: cattle; ranching; ranch; cows; Rosalia; Symphony in the Flint Hills; Liggetts; Nuttles; Dunns; Jahrens; Gottsch; trading; feedlot; feed yard; tallgrass; prairie; hills; flint hills; Bill Oates